Slovenia Teachers : SABER Country Report 2015 - Zgaga, Pavel (World Bank, Washington, DC, 2018)
Evidence on the impacts of many teacher policies remains insufficient and scattered, the impact of many reforms depends on specific design features, and teacher policies can have very different impacts depending on the context and other education policies already in place. Systems approach for better education results (SABER) teachers aims to help fill the gap by collecting, analyzing, synthesizing, and disseminating comprehensive information on teacher policies in primary and secondary education systems around the world. SABER-teachers is a core component of SABER, an initiative of the World Bank education global practice. SABER-teachers collects data on ten core areas of teacher policy to offer a comprehensive descriptive overview of the policies in place in each participating education system. To offer informed policy guidance, SABER-teachers provides an analysis of these data to assess how well each system’s teacher policies promote student achievement based on the global evidence to date. By classifying countries based on their performance in each of the eight teacher policy goals, SABER-teachers provides a diagnosis. This report presents the results of the SABER-teachers tool as applied in Slovenia.